2007
DOI: 10.1016/j.neuroimage.2006.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of BOLD, perfusion, and CMRO2 measurements with calibrated-BOLD fMRI

Abstract: The coupling of changes in cerebral blood flow (CBF) and cerebral metabolic rate of oxygen (CMRO 2 ) during brain activation can be characterized by an empirical index, n, defined as the ratio between fractional CBF change and fractional CMRO 2 change. The combination of blood oxygenation level dependent (BOLD) imaging with CBF measurements from arterial spin labeling (ASL) provides a potentially powerful experimental approach for measuring n, but the reproducibility of the technique previously has not been as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 33 publications
12
135
3
Order By: Relevance
“…These numbers are in agreement with the number of voxels detected as significantly active in this study. Despite the lower SNR, we observed a lower coefficient of variation for CBF percent signal change compared to BOLD, implying a higher reproducibility of CBF values, in agreement with previous studies (Leontiev and Buxton, 2007; Tjandra et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…These numbers are in agreement with the number of voxels detected as significantly active in this study. Despite the lower SNR, we observed a lower coefficient of variation for CBF percent signal change compared to BOLD, implying a higher reproducibility of CBF values, in agreement with previous studies (Leontiev and Buxton, 2007; Tjandra et al, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…Hypercapnia data were acquired for determination of the BOLD scaling factor, M, with results similar to previously reported values (Chiarelli et al, 2007a;Davis et al, 1998;Leontiev and Buxton, 2007a). Functional runs were acquired to enable the determination of an ROI within the visual cortex and to allow comparison of the coupling of CBF and CMRO 2 under the different conditions of visual stimulation and caffeine consumption.…”
Section: Discussionmentioning
confidence: 63%
“…The coupling between changes in blood flow and oxygen metabolism can be described by the ratio, n, of the fractional CBF change to the fractional CMRO 2 change. Previous calibrated-BOLD studies have typically reported a strong coupling between CBF and CMRO 2 changes during brain activation, with n values in the range 2-3 observed in the visual cortex in response to visual stimulation (Chiarelli et al, 2007a;Davis et al, 1998;Hoge et al, 1999;Kim et al, 1999;Leontiev and Buxton, 2007a). Regional differences in n across the brain have also been reported (Chiarelli et al, 2007a).…”
Section: Introductionmentioning
confidence: 97%
“…Unlike conventional T2 mapping, TRUST uses T2-preparation to modulate T2-weighting and also uses composite pulses and RF phase cycling to minimize the effect of RF imperfection on T2 value, thus the conversion from T2 to Yv is more accurate (Lu et al, 2011). Most existing noninvasive MRI techniques for CMRO 2 quantification involve special physiological challenges such as hypercapnia or hyperoxia (Chiarelli et al, 2007;Leontiev and Buxton, 2007) and/or exogenous agents (e.g., caffeine). These so-called calibrated functional MRI techniques are sensitive to changes of CMRO 2 but not to the baseline values; therefore, they may not be suitable for routine clinical studies.…”
Section: Discussionmentioning
confidence: 99%